IMPROVING PUPILS’ SELF ASSURANCE AND LITERACY IN SPEAKING THROUGH STORY TELLING AT SMP SWASTA TRIANA - Maharani, Fitria Erine; Zulfitri; Harahap, Yulia Sari (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This study investigates the effectiveness of storytelling techniques in improving students' selfassurance and literacy in speaking English at SMP Swasta Triana. The research employs a Classroom Action Research (CAR) design, involving 33 eighth-grade students. The study utilized a mixed-method approach, collecting both qualitative and quantitative data through interviews, questionnaires, and pre- and post-tests. Results demonstrate a significant improvement in students' speaking proficiency and confidence levels. Speaking skills increased from 51% in the pre-test to 72% in the first post-test, and 100% in the second post-test. Qualitative data revealed that storytelling created an engaging and comfortable learning environment, enhancing students' understanding and problem-solving skills. The storytelling technique effectively boosted students' confidence in public speaking and English language use. It also encouraged increased reading and improved English presentation skills among all participants. These findings suggest that storytelling is an effective method for enhancing English speaking skills, self-assurance, and literacy among junior high school students. This research contributes to the field of English language teaching by providing empirical evidence on the efficacy of storytelling in improving speaking skills. The study recommends that educators incorporate diverse speaking activities and creative teaching strategies, such as storytelling, to facilitate engaging and effective language learning experiences.